(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2017)
Measurement sense implies a complex process, which begins with the perception and comparison of measurable attributes, and it´s completed with measurement techniques and estimation strategies in contextualized situations. For surface area, the importance given to the use of formulas, even at early stages, in the detriment of understanding measure units, blocks the development of measurement sense. Through a teaching experiment carried out with students of fourth-grade in primary school, the potentialities and difficulties that arise when implementing a didactical sequence for introducing the surface magnitude are explored. Children work collaboratively solving contextualized tasks, aimed at fostering the understanding of the main surface area units and their relationships. Estimation and the multiplicative principle play a key role along the sequence.